Human steroid biosynthesis, metabolism and excretion are differentially reflected by serum and urine steroid metabolomes: A comprehensive review. Issue 194 (November 2019) - Schiffer, Lina; Barnard, Lise; Baranowski, Elizabeth S.; Gilligan, Lorna C.; Taylor, Angela E.; Arlt, Wiebke; Shackleton, Cedric H.L.; Storbeck, Karl-Heinz
Graphical abstract: Highlights: The serum metabolome does not reflect steroids activated in an intracrine manner. The urinary steroid metabolome reflects steroid biosynthesis and metabolism. Defined pathways link the circulating and urinary steroid metabolomes. Modern mass spectrometry techniques allow for comprehensive steroid profiling. Abstract: Advances in technology have allowed for the sensitive, specific, and simultaneous quantitative profiling of steroid precursors, bioactive steroids and inactive metabolites, facilitating comprehensive characterization of the serum and urine steroid metabolomes. The quantification of steroid panels is therefore gaining favor over quantification of single marker metabolites in the clinical and research laboratories. However, although the biochemical pathways for the biosynthesis and metabolism of steroid hormones are now well defined, a gulf still exists between this knowledge and its application to the measured steroid profiles. In this review, we present an overview of steroid hormone biosynthesis and metabolism by the liver and peripheral tissues, specifically highlighting the pathways linking and differentiating the serum and urine steroid metabolomes. A brief overview of the methodology used in steroid profiling is also provided.